Effect of mutations in puuP, ydcK, fadD and cadA genes in the generation of persistent cells in Escherichia coli (2017)
When a population of bacteria is exposed to a stress such as an antibiotic, most of the population is killed. However, there is a small fraction of slow growing cells stochastically formed that can survive and become a new population, still susceptible to the antibiotic. This phenomenon is called bacterial persistence. Given the importance of this type of cells in clinical environments, there is a need to understand their nature and discover the different factors that trigger their formation. In a previous study, using genomics and transcriptomics on the Escherichia coli DS1 (hipQ) strain, a high type II persistence mutant, four mutations in the puuP, ydcK, fadD and cadA genes were identified as candidates for accounting for the hip phenotype. The aim of this study was to study the role of each mutation alone or in combinations with others in a clean TH1268 genetic background. For this, transformed strains were created to study the effect of these mutations...